Characterization of anti-inflammatory effect and possible mechanism of action of Tibouchina granulosa. (8th March 2017) - Sobrinho, Andrea P; Minho, Alan S; Ferreira, Leide L C; Martins, Gabriel R; Boylan, Fabio; Fernandes, Patricia D
Abstract: Objectives: Tibouchina granulosa, popularly known as 'quaresmeira', belong to a genus widely used in the traditional medicine as infusions from their leaves. Other species of Tibouchina are used as antibacterial, antioxidant or antileishmanial. In this work, our objectives were to investigate the biological effects of T. granulosa in models of acute inflammation. Methods: Chemical analysis showed the presence of proanthocyanidins and flavonoids. Infusions from leaves of T. granulosa (1, 3, 10, 30 or 100 mg/kg) were orally administered to mice, and the anti-inflammatory effects were evaluated by the formalin-induced licking response, inhibition of carrageenan-induced cell migration into subcutaneous air pouch (SAP) and inhibition of inflammatory mediator production in inflammatory exudate collected from SAP. Key findings: Our data indicate that tested doses of T. granulosa infusion reduced cell migration, protein extravasated to SAP and cytokine production (i.e. TNF-α and IL-10). All doses also inhibited the first and second phase of formalin-induced licking response. Conclusions: Taken together, our results indicate that leaves of T. granulosa present anti-inflammatory effect and can be useful in the preparation of new phytomedicines.